KARAKTERISTIK HABITAT DAN POTENSI KEPITING BAKAU (Scylla serrata, S.transquaberica, and S.olivacea) DI HUTAN MANGROVE CIBAKO, SANCANG, KABUPATEN GARUT JAWA BARAT - Irvan Avianto; Sulistiono Sulistiono; Isdrajad Setyobudiandi (Jurusan Perikanan dan Kelautan, 2013)
The research aimed to collectdata and information about the habitatcaracteristics and mud crabs potency in Cibakomangrove forest. Sampling was conductedthrough line plot transect survey.Parameters examined physical-chemical characteristic,mangrove vegetation, mud crabspopulation and size distribution. Habitatcharacteristics were collected cluster analisys.The result showed that some parametersof habitat were resemblance wherestations 1 and 2 were Groups A, stations3 and 4 were groups B , and station 5 and6 were groups C. The mud crabs populations,size distribution, and habitat groupswere analyzed correspondence analysis.S.serrata dominate in zone A in dark totaled67 ind. individual existence S.serrataallegedly tolerant of high salinity > 28 0/00and macrozoobenthos abundance of mangrovecrabs as a food source. S.tanquabericadominate in zone B in the dark was 70 ind.The presence of individual species in zoneB allegedly tolerant of salinity 24 -> 280/00, natural food abundance and habitatsuitability as a mud substrate. S.olivaceadominate in the zone C in the dark totaled38. The presence of individual speciesin zone C allegedly due to low salinity tolerant in the range of 21-22 0/00 and canlive on clay substrate.